Studi Komparatif Efektivitas Seftriakson dibanding Kombinasi Seftriakson-Metronidazole dan Sefuroksim-Metronidazole pada Pasien Apendisitis yang Menjalani Apendiktomi - Zulfa, Ilil Maidatuz (Jurnal Farmasi Udayana, 2020)
Appendicitis or inflammation of appendix still has high prevalence in Indonesia which reach 3236 cases in 2103 and increase at 4351 cases in 2014. Antibiotics are used in appendicitis to prevent surgical site infection (SSI) after appendictomy. Cephalosporins like ceftriaxone and cefuroxime are commonly used as monotherapy or in combination with imidazole. This study was aimed to compare the effectifity of antibiotics used in acute appendicitis non perforation using parameter length of hospital stay, discharge status, and amount of SSI occurence. An analytical observation was conduct retrospectively through acute appendicitis patient medical records with ICD k35.8 during 2018. A total of 39 medical records were analyzed. Of that, 25 patients received ceftriaxone monotherapy, 5 patients received combination of ceftriaxone and metronidazole, and 9 remaining received cefuroxime in combination with metronidazole. All antibiotics were administered intravenously and used as prophylaxis and continued as pasca appendictomy therapy. The average of hospital stay of that three antibiotics regimen showed that the patients received combination of cefuroxime and metronidazole had the shortest period (3.00 + 0,50 days) while based on discharge status, patients with ceftriaxone monotherapy were the most who discharged to home with complete recovery (64.00%). However, SSI occurence was only observed in patients received ceftriaxone monotherapy (2.00%). Statistical analysis showed that there is a significant different in the average of hospital stay and discharge status through three groups of antibiotics treatment (p- value 0,000; p- value 0,001). In conclusion, the three regimens of antibiotics are effective as prophylactic and post appendictomy in acute appendicitis. However, becuse of significant difference of hospital stay, antibiotics regimen selection should consider the cost and effectivity ratio analysis.